EXPERIMENTAL INVESTIGATION OF HEAT TRANSFER IN A RECUPERATOR OF A CONVECTIVE DRYER - Чалаев, Джамалутдин; Дабижа, Наталья; Малащук, Наталья (SWorldJournal, 2021)
The issue of increasing the energy efficiency of condensing heat pumps, which are used in convective drying devices with the closed circulation of the drying agent, was considered. In these devices, moisture from the volume of the drying chamber was remov